2012
DOI: 10.1373/clinchem.2011.177626
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Mental Retardation 1 (FMR1) Intron 1 Methylation in Blood Predicts Verbal Cognitive Impairment in Female Carriers of Expanded FMR1 Alleles: Evidence from a Pilot Study

Abstract: BACKGROUND:Cognitive status in females with mutations in the FMR1 (fragile X mental retardation 1) gene is highly variable. A biomarker would be of value for predicting which individuals were liable to develop cognitive impairment and could benefit from early intervention. A detailed analysis of CpG sites bridging exon 1 and intron 1 of FMR1, known as fragile Xrelated epigenetic element 2 (FREE2), suggests that a simple blood test could identify these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
49
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 37 publications
8
49
3
Order By: Relevance
“…13 In Figure 2, we show that in a larger cohort, the 0.435 methylation threshold can separate FM individuals from PM and control groups as effectively in 500 ng of DNA from venous blood as in cell extract from one 3-mm punch per sample from dried blood spots of adults and newborns. …”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…13 In Figure 2, we show that in a larger cohort, the 0.435 methylation threshold can separate FM individuals from PM and control groups as effectively in 500 ng of DNA from venous blood as in cell extract from one 3-mm punch per sample from dried blood spots of adults and newborns. …”
Section: Discussionmentioning
confidence: 90%
“…We found that by including the Y chromosome marker with a 0.435 MOR FXS methylation threshold, 13 almost all sex chromosome aneuploidies could be differentiated with sensitivity and specificity approaching 100%. The exceptions were one 49,XXXXY and two 47,XXX individuals who could not be differentiated from control females.…”
Section: Using the Free2 Methylation Test For Combined Fxs And Sex Chmentioning
confidence: 88%
See 3 more Smart Citations